Heart Rate Variability Differs between Right- and Left-Handed Individuals. Issue 3 (June 2014) - Yüksel, Ramazan; Arslan, Muzeyyen; Dane, Şenol
Previous studies reported reduced longevity in left-handers with the suggestion that it may be associated with different heart diseases. Therefore, differences in heart rate variability (HRV), an index of autonomic cardiac activity, were examined for right- and left-handed individuals. 120 healthy young university students (75 women, 45 men; M age = 20.4 yr., SD = 1.5) volunteered. Handedness was assessed with the Edinburgh Handedness Inventory and HRV was measured via electrocardiography. The results suggest that the left-handers' HRV was significantly different from that of right-handers on several parameters. The atypical cerebral organization of left-handers may be related to an imbalanced autonomic system that results in higher frequencies of heart irregularities.